The international 2nd edition Colloquia Bibliothecariorum FAINA TLEHUCI IN MEMORIAM February 27, 2014 (Confluenţe Bibliologice, 2025)
The Scientiﬁc Library has hosted the International 2nd edition Colloquia Bibliothecariorum FAINA TLEHUCI IN MEMORIAM on February 27, 2014. The colloquia was attended by representatives from national and international librarian community. Remarkable event was dedicated to Faina Tlehuci, the ex-director, who built with her own hands, heart and soul the library for 40 years. The plenary session included a meeting „Faina TLEHUCI in Contemporaries” Memory”. The two sections were composed  from: The Library Collections are the pride of a true librarian; Libraries of the future has endless possibilities included 19 communications, Launching the ﬁrst edition of Colloquia Bibliothecariorum  materials (23 February, 2013); A video ﬁlm about Faina  Tlehuci, the Honorary Member of the Senate (October 8, 2001), Hearing her speech  from  an audio cassette recorder  presented by her to 50 years of Scientiﬁc Library  in 1995 with the title ,,the most urgent problem today is completing the library collection with books in Romanian language” .
Keywords: Colloquia Bibliothecariorum